A flexible and effcient microscopic simulation of multiple GEM chamber based on Garfield++. (April 2020) - Bellini, V; Brio, V; Cisbani, E; Kmieć, K; Lagamba, L; Perrino, R; Petta, C; Re, L; Sutera, C
Abstract: Microscopic simulations may bring a better understanding of the response of gaseous detectors. Such simulations are computationally demanding, due to the modelling of the low energy processes and to the high segmentation required for the 2D/3D field maps. In MPGD such maps can be much more complex than those of traditional multiwire chambers, due to the heterogeneous materials and more involute geometries, which break the simplifying symmetries featured in the latter. In order to investigate the performance of the triple GEM 2-dimensional tracking chambers being developed for high luminosity experiments with the Super BigBite Spectrometer at Jefferson Laboratory, we have set up a flexible and rather effcient multistep simulation processor based on either ANSYS or GMSH+ELMER for 3D CAD and electrostatic field modelling and then combined to Garfield++. Potential systematic effects from the 3D CAD modellers, the mesh generators and the electrostatic field solvers have been estimated with dedicated simulations; once these effects have been assessed, the results of the multistep approach have been compared to a simplified whole GEM chamber model.